PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PROJECT BASED LEARNING PADA SISWA KELAS X IPA-4 SMA NEGERI 1 KOTA TIDORE KEPULAUAN - Nurafni Achmad (Jurnal Geocivic, 2020)
Project based learning (PBL) using the PBL model can improve students' ability to understand mathematical concepts. In terms of student learning completeness, classically, it has achieved ideal learning completeness, which is 100% of the total number of students who complete their study on the subsumative test, and the average test score obtained by students has increased for each action project based learning (PBL). Judging from each category the level of understanding of mathematical concepts, in the category of understanding the whole has increased each cycle. Meanwhile, the percentage of students who had partial misconception, misconception and did not understand from the high category gradually decreased to low because most students had entered the category of fully understanding and partly understanding. This shows that generally students have understood the material being studied. Students' attitudes towards project based learning (PBL) using the PBL model are generally positive. Students feel happy and interested because by using the PBL model learning mathematics becomes less monotonous and more enjoyable so that students find it easier to understand the material being taught.